Feasibility and concurrent validity of a cardiorespiratory fitness test based on the adaptation of the original 20 m shuttle run: The 20 m shuttle run with music - Lamoneda, J.; Huertas-Delgado, J. H.; Cadenas-Sanchez, C. (Journal of Sports Sciences, 2020)
The purpose was to examine the feasibility of the 20m shuttle run test with music and to test its concurrent validity with the original 20m shuttle run test. A total of 386 adolescents (14.5±1.6 years old, 48.9% boys) participated in our study. A self-reported questionnaire was used to assess student`s perception about the 20m shuttle run test with music and the original and to assess perceived exertion. Participants performed randomly the 20m shuttle run test with music and original two weeks apart. Average and maximum heart rate were monitored with heart rate monitors. The 20m shuttle run with music was a feasible test for measuring cardiorespiratory fitness in adolescents. The concurrent validity showed mean differences of 5.1±14.6 for shuttles, 0.3±0.8 km/h for speed, 0.5±4.1 for stages, and 1.5±4.1 for VO2max (all p<0.001) in favour of the 20m shuttle run with music vs. the original 20m shuttle run test. Mean difference for the rating of perceived exertion was 0.4±2.5 points (p=0.003). No significant difference was found between boys and girls. In conclusion, the 20mSRT-music is feasible and presents a good concurrent validity in adolescents, independently of the sex and it will be an alternative and good approach to assess cardiorespiratory fitness.